Ways to hold national action games with kindergarten children - A.Sh.Usmonov (Research Parks Publishers, 2021)
According to the content of preschool pedagogy, kindergartens and the requirements of physical education, children of kindergarten age are divided into different age groups and are called small, medium and large groups